Kingdom of Lesotho : Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Extension of the Arrangement and Rephasing of Disbursement. (IMF Staff Country Reports; Country Report, 2013)
The Extended Credit Facility (ECF) program extended to Lesotho after a sharp fall in revenues remained broadly on track. Lesotho maintained positive growth supported by expansion of mining and construction. Fiscal consolidation efforts have helped to strengthen international reserves, despite weak diamond prices. Executive Directors welcomed the government's continued efforts to improve the business climate and promote private sector development. They also suggested the need to maintain fiscal consolidation efforts, while safeguarding priority social and growth-promoting capital spending.